Mealtime Difficulties - Stapleton, Denise; Griffiths, Gillian; Sherriff, Jillian (PTM Publishers Limited, 2012)
Frequent or complex mealtime difficulties can have adverse effects on relationships within families.Such issues require community based prevention and early intervention to optimise the emotional well-being of families. This article describes the relational component of mealtime difficulties, the effects on the emotional wellbeing and family relationships and the perceived needs of families for new service developments at a community level. In contrast to most of the literature regarding mealtime difficulties, which focus on behaviour training, parenting skills and nutrition education, this article concludes that the primary aim of an intervention for mealtime difficulties in the community should be to optimise interactions and relationships within families through a holistic, interdisciplinary approach.